Analisis Strategi Pemasaran pada PT Telkom Tbk - Shintami Oktavia; Muhammad Baihaqi; Zaky Asdhika Sinaga; Teddy Ramaditya; Henriadi Hasibuan; Aldi Lumbanraja; Sri Ningsih Karnance; Hanna Maria Siagian (Journal on Education, 2025)
Information in a company is very important to support its continued development, so there is a reason that information is very much needed for a company. One of the companies that uses an integrated information system network to facilitate the running of the company's business is PT. Telkom is required to further improve the quality and quantity of its services in order to become the best telecommunications company in Indonesia and even the world, not only that, PT Telkom also realizes that there is an important role for human resources (HR) in helping the company to achieve its main goals, and in helping the company to achieve its main goals, and in its implementation must consider social, functional and employee interests.